2017
DOI: 10.1038/s41598-017-09169-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and Lipidomic Profiling Identifies The Role of the RNA Editing Pathway in Endometrial Carcinogenesis

Abstract: Endometrial cancer (EC) remains the most common malignancy of the genital tract among women in developed countries. Although much research has been performed at genomic, transcriptomic and proteomic level, there is still a significant gap in the metabolomic studies of EC. In order to gain insights into altered metabolic pathways in the onset and progression of EC carcinogenesis, we used high resolution mass spectrometry to characterize the metabolomic and lipidomic profile of 39 human EC and 17 healthy endomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 49 publications
1
46
0
Order By: Relevance
“…Pooled quality control (QC) samples were composed with 10% volume of each sample. Lipids were resolved using Acquity UPLC CSH 1.7 µm, 2.1 × 100 mm column (Waters Corp. Milford, MA, USA) with a gradient described previously [ 22 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pooled quality control (QC) samples were composed with 10% volume of each sample. Lipids were resolved using Acquity UPLC CSH 1.7 µm, 2.1 × 100 mm column (Waters Corp. Milford, MA, USA) with a gradient described previously [ 22 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…additionally, using next-generation sequencing transcriptomics, chan et al (40) reported that ADARB1 contributed to inhibitory mechanisms in gastric cancer via its catalytic deaminase. However, altadill et al (41) demonstrated that ADARB1 was upregulated in endometrial cancer, and the increased expression was positively associated with disease aggression, suggesting that ADARB1 functions as an oncogene in endometrial cancer. The inconsistency between the observations of these aforementioned studies and the present study may be due to the diverse pathological states of different diseases; therefore, further investigation is required.…”
Section: Discussionmentioning
confidence: 99%
“…BOLL functions as an oncogene because of enhancing proliferation and migration activities in the colon cancer cells, and BOLL protein expression was upregulated in colorectal cancer tissue [36]. ADARB1 was expressed at high levels in endometrial cancer, and observed a positive correlation between increased expression and invasion degree [37]. Another study reported that ADARB1 could inhibit glioblastoma cell growth via regulation of the CDC14B/Skp2/p21/p27 axis [38].…”
Section: Discussionmentioning
confidence: 99%